Evaluation of the psychometric properties of the Short Grit Scale (Grit-S) for Iranian dental students - Saman Jalali; Omid Saed; Kamyar Mansori; Azin Nourian (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Non-cognitive and personality variables, such as grit, have been shown to play an important role in medical science education. In order to facilitate studies in this field, it is necessary to have a reliable and valid instrument. The purpose of this study was to evaluate the factor structure and psychometric properties of the short Grit Scale (Grit-S) for Iranian dental students. Material & Methods: For this psychometric study, the short Grit-S was administered to a sample of dental students (n = 226) during the first semester of the academic year 2022-2023 at the School of Dentistry of Zanjan University of Medical Sciences. First, the questionnaire was translated, and then the psychometric properties of the Short Grit-S were evaluated. Descriptive statistics and Exploratory Factor Analysis (EFA) were performed using SPSS 26, while Confirmatory Factor Analysis (CFA) was conducted through AMOS 24. Results: The results of this study provide evidence for the validity and reliability of the Short Grit-S as a measure of grit among Iranian dental students. The internal consistency coefficient (Cronbach's alpha), split-half reliability, and test-retest were 0.80, 0.82, and 0.84, respectively. The Short Grit-S was found to be a valid and reliable instrument with good factorial validity, internal consistency, convergence, and criterion validity. The Short Grit-S was found to be useful for finding out how persistent Iranian dental students were in their efforts (Eigenvalue 3.53; variance explained 50.44) and how interested they were in learning (Eigenvalue 1.16; variance explained 16.55). The two-factor model with 7 items (item 2 was omitted) was found to be the best factor structure for the Persian version of the Short Grit-S. Conclusion: In conclusion, the study found that the Persian version of the Short Grit-S with 7 items was a reliable and valid instrument for measuring grit among Iranian dental students.